Code of ethics to accountants and auditors - Dias, Cristiana (2015)
Code of ethics is an essential tool in the battle against fraud and corruption. Accountants and auditors are the first SMEs' advisers on a wide range of subjects from accounting to auditing. Indeed, codes of ethics are classified as strategic management tool and the process of change lead to the need to do it in a sustainable development which generates gains for the society, in general, and SME, in particular. This research presents a theoretical framework that allows to discuss the importance of the code of ethics in order to achieve appropriate level of knowledge and attitudes in business ethics. The empirical framework based on SME database, but for the accounting and auditing services, in order to promote, at exploratory level, two different perspectives: Portuguese and Italian. The results of this research allow us to conclude that the SME must design new strategies and challenges to answer, on the one hand, to new market targets and ethical demands of clients. And, on the other hand, to increase value that became essential to the SME sustainability. Indeed, this research identifies two different perspectives: Portuguese and Italian that highlight the strategic approaches followed in the recognition of the importance of the code of ethics, as well as, social responsibility strategies which will increase, at internal level, the engagement of stakeholders to the SME and, at external level, to the society.